PENGEMBANGAN MEDIA MINECRAFT EDUCATION EDITION UNTUK MENUNJANG KEMAMPUAN TPACK MAHASISWA - Bastian, Titus Agung; Soepriyanto, Yerry; Duananda Kartika Degeng, Made (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2025)
This research aims to produce Minecraft learning media that can support students' TPACK skills. This research was conducted in the Learning class at State University of Malang with a total of 97 students from various majors, namely guidance and counseling, chemistry, PGPAUD (Early Childhood Education Teacher Education), special education, art and design, and educational technology with the number of classifications based on gender, namely 79 female students and 19 male students. The model used in this research is the development model according to Lee & Owens with the stages of assessment/analysis, design, development, implementation, and evaluation. The data collection process was carried out by distributing questionnaires and analyzed using the highest average according to Sugiyono. The results showed that Minecraft Education media to support students' mastery of TPACK was declared feasible based on content experts, and media experts. The content expert validation score gets an average score of 5.00 while the media expert gets an average score of 4.75 so this media is declared feasible. This media also received good responses regarding whether there was an increase in how to integrate Minecraft Education technology in learning based on the questionnaire that had been distributed and received a score of 3.34 from the expected average value of 4.00.